Toroidal Dipole Resonances in All‐Dielectric Oligomer Metasurfaces. Issue 10 (16th August 2019) - Zhang, Guanqiao; Lan, Chuwen; Gao, Rui; Wen, Yongzheng; Zhou, Ji
Abstract: Dynamic toroidal multipoles have been attracting an increasing amount of attention, thanks to their unique electromagnetic properties. The concept bears great promises in the field of optical sensing as well as electromagnetic energy localization. Metal‐based structures with specific designs have been widely adopted to obtain toroidal responses. However, applications for such structures are often hindered by the significant intrinsic loss when it comes to optical frequencies. Here, several configurations of all‐dielectric metasurfaces, in which the meta‐molecules are composed of disk oligomers (trimer, quadrumer, pentamer, and hexamer), are proposed to support toroidal dipole resonances in the near‐infrared waveband when the polarization of the normally incident excitation plane wave is directed to one of the symmetry axes of the oligomers. Multipole expansion including the toroidal dipole term along with near‐field electromagnetic patterns confirms the existence of strong toroidal dipolar responses within certain wavelength ranges. This work would enrich the diversity of the all‐dielectric optical systems with toroidal dipole resonances. Abstract : The inclusion of dynamic toroidal dipole term in multipole expansion is necessary for analyzing electromagnetic responses of a plethora of artificial structures. In this paper, several kinds of all‐dielectric metasurfaces composed of oligomer clusters are investigated. It is shown that these structures could support toroidal dipole resonances, which is confirmed by multipole expansion calculations and near‐field simulation patterns.